Mathematics
juliayagodinski
2015-11-05 12:40:54
Simplify this problem -6y+12+7y-5
ANSWERS
Geena
2015-11-05 18:33:11

We want to simplify -6y + 12 + 7y - 5 Collect the terms that involve y. -6y + 7y is the same as 7y - 6y = y Explanation: Suppose y represents an apple. If you have 7 apples (7y) and you give away 6  apples (-6y), then you have one apple left (1y or y). Collect the constant terms together. +12 - 5 = 12 - 7 = 7 Therefore -6y + 12 + 7y - 5 = (7y - 6y) + (12 - 5) = y + 7 Answer: y + 7

ADD ANSWER